THE AUSTRALIAN INTANGIBLE STANDARD (AAS 18/AASB 1013):CRITICS AND VIEWS - Shahwan, Yousef (Akutansi Bisnis & Manajemen ( ABM ), 2004)
Accounting for intangibles has been subjects of controversy in Australia and in manyother countries (Grant, 1996). The Australian goodwill standard (AAS 18/AASB1013)requires goodwill to be capitalised and amortised over a maximum period of twentyyears. However, there has been no specific accounting standard governing accountingfor identifiable intangible assets in Australia. Such regulatory position has recentlybeen criticised by the profession as well as academicians. This paper analyses someof these critics and views that are of interest to accounting for intangibles. It was foundthat much of the Australian research work on intangibles has focused on how goodwilland identifiable intangible assets are kept in accounts by the Australian companies andthe impact of amortisation requirements in AAS 18/AASB 1013. Thus, it can beconcluded that more empirical work isneeded to examine the reaction of the Australiancapital market to disclosures of goodwill and identifiable intangible assets.